MAKNA PENDIDIKAN BAGI ANAK USIA SEKOLAH DI KAMPUNG PULAI KENAGARIAN LAKITAN TENGAH KECAMATAN LENGAYANG KABUPATEN PESISIR SELATAN - Putri, Novrici Mandella; Adiyalmon, Adiyalmon; Elfemi, Nilda (Pendidikan Sosiologi, 2013)
This reasearch have a background by different perception about educatio in school age, schoolchild explaning the meaning of education with other purpose, it see from their attitude when coming late to school, do not doing the tasks from teachers and penetrated in school. But, government, school and parents have doing everthing ways to increase education quality. The objective of this research is to know and description 1). cause of child is lazy to follow learning process, 2). the meaning of education for schoolchild.The theory in this research is phenomenon theory by Alfred Schutz. Method of this research use qualitative approach. With descriptive research for description problemâs of research. Taking of participation use purposive. Participation from this research is students in senior high school. The data is primary and secunder data. Data collective by interview technique, observation and documentation, with using tools like instruction and interview, book, pen, and handphone. All of data will analyze with reduction data, display data and verification data (summary).The result of this research is 1). cause of child is lazy to follow learning process are: a). internal factor, low of interest child to study. b). eksternal factor, consists of: 1. family evironment factor, is cause of habit and parentâs education background. 2. school environment factor, is docrease of dicipline, influence of friends and method of teacher when teaching students in the class. 3. community environment factor, especially mass media influence like internet, playing and entertain place. 2). the meaning for schoolchild are: a). as an activity to far away fom homework and get the pocket money. b). as an activity to meet with friends and far away from people in village. c). as a media to get certificate.